Agreement of ultra-short-term heart rate variability measure after different repeated bouts of sprint ability tests - Hung, Chin-Hwai; Lu, Wan-An; Pagaduan, Jeffrey Cayaban; Kuo, Cheng-Deng; Chen, Yung-Sheng (Science progress, 2024)
This study aims to explore: (1) the validity of post-exercise ultra-short-term heart rate variability (HRVust) after two different bouts of repeated sprint ability test (RSA), and (2) the relationship between HRVust measure and RSA performance. Twenty adolescent male futsal players voluntarily participated in this study (age: 17.65 ± 1.81 years, body height: 170.88 ± 4.98 cm, body weight: 61.78 ± 4.67 kg). The participants performed a standard RSA test (RSAstandard) and an RSA test with a 10% decrement of the best sprint time test (RSA10%decrement) on two separate occasions within a week. On both occasions, a 5-min resting electrocardiography was administered pre- and post-RSA exercise protocols. The first 30-s (HRVust30s), 60-s (HRVust60s), and 60-120-s (HRVust1-2min) were extracted and used to compare with the standard of 5-min HRV recording (HRVcriterion). The natural logarithm (ln) of the standard deviation of normal-to-normal intervals (SDNN) and root mean square of successive normal-to-normal interval differences (RMSSD) HRV indices were utilised to establish intraclass correlation coefficient (ICC2,1), coefficient of variation (%CV), and Pearson product-moment correlation (r). Results revealed the ICC values of HRVust lnSDNN (RSAstandard = 0.77-0.88; RSA10%decrement = 0.41-0.71) and lnRMSSD (RSAstandard = 0.81-0.86; RSA10%decrement = 0.57-0.82). Furthermore, significantly positive correlations between best sprint time and post-exercise HRVust indices were found in lnSDNN (r = 0.47-0.62; p < 0.05) and lnRMSSD (r = 0.45; p < 0.05). Additionally, a large CV of lnSDNN (RSAstandard = 32%-45%; RSA10%decrement = 29%-39%), lnRMSSD (RSAstandard = 50%-66%; RSA10%decrement = 48%-52%), and ratio (RSAstandard = 45%-126%; RSA10%decrement = 27%-45%) was found after the RSA protocols. In conclusion, the number of bouts of RSA exercise potentially influences the agreement of post-exercise time-domain HRVust indices to standard HRV measure.
Keywords: elektrokardiografie; Exercise Test; cvičení; mladiství; exercise recovery; Running; mužské pohlaví; autonomic nervous system; Heart Rate; srdeční frekvence; time-domain measure; Electrocardiography; Humans; parasympathetic activation; zátěžový test; sportovní výkon; Exercise; Athletic Performance; běh; Cardiac-related responses; Adolescent; lidé; Male